Pharmacoeconomic aspects of further improvement of pharmaceutical care for patients with depressive disorders - Khaliq, R.; Yakovleva, O. S.; Яковлева, Ольга Станіславівна (Запоріжжя : ЗДІА, 2016)
In modern society among general medical problems the most urgent are the problems of depressive disorders. According to WHO, at the beginning of the XXI century depressive disorders accounted for about 40% of total mental pathology. Every year depression affects about 200 million people, and this figure is rapidly growing. Every eighth person, at least once in life, requires specialized antidepressant therapy (WHO, 2000). Among general population of patients seeking for medical or psychological help, depressive disorders are recorded in 65% of cases.